MSCs regulate oxidative stress through the Nrf2 pathway to treat chronic obstructive pulmonary disease - Yunchun Zhou; Wenrui Zhou; Yinghua Li; Jing Zhang (BMC Pulmonary Medicine)
Abstract Background Chronic obstructive pulmonary disease (COPD) has become a great public health concern. While existing treatments can provide relief from COPD, they do not cure the disease. Stem cell transplantation is an emerging treatment modality that may play an important role in COPD treatment. Methods A COPD model was constructed by exposing mice to tobacco smoke and administering bacterial lipopolysaccharide via intranasal drops. The progression of COPD was monitored after the transplantation of MSCs, and oxidative stress-related pathways were evaluated to explore the relationship among COPD, oxidative stress and stem cell transplantation. HE staining and Masson’s trichrome staining were used to detect pulmonary lesions and the degree of pulmonary fibrosis. The levels of oxidative stress-related molecules were evaluated via qRT‒PCR and ELISA. Nrf2 pathway molecule expression was detected by immunofluorescence. Results Compared with the control group, we successfully established a tobacco smoke-induced COPD model with an increased lung macrophage number, inflammatory cell infiltration, enlarged alveoli, and pulmonary fibrosis. After MSC transplantation, the oxidative stress level was reduced, and the lung condition improved, 4-HNE in COPD mice decreased by 90pg/mg prot, IL-6 decreased by 15.55pg/ml, ROS decreased by 1.9 × 107, PCT in the blood decreased by 0.51 µg/L, EOS decreased by 29.02%, and WBC decreased by 3.41^9/L. CRP decreased by 15.8 mg/ml. In addition, our data suggest that MSCs may mitigate lung injury from COPD by reducing oxidative stress through the regulation of the Nrf2 pathway. Conclusion This study confirmed the therapeutic effect of transplanted MSCs on tobacco- and lipopolysaccharide-induced COPD and revealed that MSCs ameliorate COPD by regulating oxidative stress-related pathways. Clinical trial number Not applicable.